The Influence of Booklets and Audiovisual Media on Breastfeeding Mothers' Knowledge of Exclusive Breastfeeding: A Literature Review - Muliatul Jannah; Rokhaitul Jannah (Jurnal Multidisiplin Sahombu, 2026)
Background: The national exclusive breastfeeding rate has not yet reached the 80% target, a factor partly attributed to a lack of information from healthcare professionals. Current education is limited to basic explanations, without comprehensive guidance or counseling on breastfeeding techniques, lactation management, and how to address breastfeeding issues. As a result, mothers lack understanding of how to maintain exclusive breastfeeding and are easily hesitant when faced with difficulties. Therefore, effective health education with appropriate media is needed to increase mothers' knowledge about exclusive breastfeeding. Booklets and audiovisual media are effective media for increasing the knowledge of breastfeeding mothers because they combine important points with images, stimulate learning, appeal to many senses, and support affective, cognitive, and psychomotor aspects. Objective: To examine effective educational media to increase mothers' knowledge about exclusive breastfeeding with a combination of booklets and audiovisual media. Methods: This research aims to examine effective educational media to increase mothers' knowledge about exclusive breastfeeding with a combination of booklets and audiovisual media. This review used a systematic search of databases such as PubMed and Google Scholar, covering articles from 2020 to 2025. After screening, 13 articles (7 national and 6 international) were selected from the initial 62 articles. The search keywords were "exclusive breastfeeding," "booklets and audiovisuals," "knowledge," and "breastfeeding mothers. Result: The review of the articles presented shows that booklets and audiovisual media have an influence on increasing mothers' knowledge about exclusive breastfeeding. Based on this research can be concluded that  booklets and audiovisual media are effective in increasing knowledge about exclusive breastfeeding by delivering information in an interesting and easy-to-understand manner. These media also support the affective, cognitive, and psychomotor aspects, so that mothers are more confident and consistent in implementing correct breastfeeding practices.